A note on parameter identification of the AISI 304 stainless steel using micromechanical-based phenomenological approaches - Vaz M.* (2019)
© 2019 Universidade Federal de Sao Carlos. All rights reserved.Austenitic stainless steels have largely been used in industrial equipment, architectural components and consumer items amongst others. Numerical simulation of manufacturing processes of such components and parts requires adequate hardening descriptions and accurate inelastic parameters. This work addresses these issues for the AISI 304 stainless steels based on phenomenological approaches using a higher order logarithmic yield stress equation and alternative micromechanical-based equations. Identification of the inelastic parameters is performed by either curve-fitting strategies or optimization techniques. The experimental-numerical comparative assessments demonstrate that the micromechanical-based yield stress equation derived from Bergström's dislocation model provides the best hardening description.